Peningkatan Kualitas Warna Dan Pertumbuhan Ikan Lemon Siklid (Neolamprologus Leleupi) Dengan Pakan Buatan Yang Diperkaya Tepung Bunga Marigold (Tagetes Erecta) - Adawiyah Mustapa; Mulis; Arafik Lamadi (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Lemon cichlid fish has the Latin name (Neolamprologus leleupi) is one of the ornamental fish species with a promising level of potential. The brightness of the color of lemon cichlid fish (Neolamprologus leleupi) is one of the important factors that must be considered by lemon cichlid fish farmers. This is because the brighter the color of the lemon cichlid fish, the higher the selling price, thus affecting the income of lemon cichlid fish farmers. Efforts to increase the brightness of the color of the fish can be done by adding carotenoids derived from marigold flowers (Tagetes erecta) which are mixed into the feed. The use of marigold flower flour (Tagetes erecta) in feed to improve the color of lemon cichlid fish has not been widely carried out, so this study was conducted. This study aims to determine the addition of marigold flower flour to fish feed can provide a real effect. The method used in this study is an experimental method with a completely randomized design (CRD). The main treatment carried out was the provision of marigold flower flour with different doses, namely: 1%, 2%, 3% and one control treatment (without the provision of marigold flower flour). The addition of Marigold flower flour did not give any significant effect based on the results obtained.